‘I can speak on this here’: empowerment within an Aboriginal adult literacy campaign - Williamson, Frances; Boughton, Bob (The Australian Journal of Indigenous Education, 2020)
Abstract This case study details the impacts of an Aboriginal-led adult literacy campaign in Brewarrina between 2015 and 2017. Forming part of a wider investigation into literacy as a social determinant of health, the study explores the relationship between involvement in the literacy campaign and the capacity of graduates to take greater control of the conditions affecting their lives. Empowerment is used here as the central explanatory construct despite robust criticism of theoretical slippage. We argue that empowerment remains relevant particularly in the context of ongoing and entrenched disenfranchisement of the low-literate in Australian Aboriginal communities. Drawing on in-depth ‘yarning’ interviews, we find strong evidence of individual empowerment among graduates of the adult literacy campaign, particularly in terms of increased self-control and confidence. However, collective change such as increased participation and organisation at the community level is less apparent. This finding underscores two important aspects of empowerment. Firstly, like learning to read and write, the task of regaining personal and collective power can be a slow and difficult undertaking. Secondly, achieving empowerment is intimately linked to addressing the causes of disempowerment. This ultimately means tackling those power relations which impact choices, opportunities and well-being beyond the borders of individual's lives and communities.